Aplikasi Pengembangan Metode Spektrofotometri UV-Vis pada Analisis Simultan Isoniazid (INH) dan Vitamin B6 di dalam Sediaan Tablet - Nasution, Lisda Rimayani; Muchlisyam; Effendy De Lux Putra (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Primary antituberculosis as the standard therapy of tuberculosis are often used in combination dosage form. It’s used to obtain effectiveness treatment and prevent the emergence of resistance. One form of this combination is a combination of INH and vitamin B6. This combination aims to prevent the side effects of INH, namely peripheral neuritis. The combination could give problems in quality control. The aims of this research is to develop a spectrophotometric method by mean centering of ratio spectra to analysis simultaneous isoniazid and vitamin B6 in tablet dosage form without prior separation. Research carried out by development of spectrophotometric method to applied determining the levels of isoniazid and vitamin B6 in tablet by mean centering of ratio spectra. Then, tested its validity based on linearity, accuracy, precision, LOD and LOQ. The results showed that applications mean centering of ratio spectra technique on assay of isoniazid and vitamin B6, have successfully applied to analyze pharmaceutical formula simultaneously with no interference from excipients as indicated by all validation parameters were within the acceptable range.